2019
DOI: 10.1055/s-0039-1694750
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Expectations of an Inpatient Portal for Hospitalized Patients and Caregivers

Abstract: Background Patient portals are intended to engage patients and enhance patient-centered care. Recent studies suggest that the information within portals could provide benefits to patients and their caregivers during hospitalization; however, few studies have examined nurse and staff expectations of portals when used in the hospital setting. Objective This article examines inpatient nurse and support staff expectations of a commercially available inpatient portal prior to its hospital-wide implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…1,2,21 Yet getting portals into the hands of hospitalized patients in a reliable manner remains a challenge for many hospitals. 8,11,12 Our findings suggested that the three strategies of establishing provisioning processes, having persistent unit-level champions, and actively promoting the distribution and use of MCB tablets can make a difference in unit provisioning performance. Notably, our study results suggest the need to further add to the list of work-related tasks falling to nursing staff who should prioritize, champion, and promote tablet provisioning.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…1,2,21 Yet getting portals into the hands of hospitalized patients in a reliable manner remains a challenge for many hospitals. 8,11,12 Our findings suggested that the three strategies of establishing provisioning processes, having persistent unit-level champions, and actively promoting the distribution and use of MCB tablets can make a difference in unit provisioning performance. Notably, our study results suggest the need to further add to the list of work-related tasks falling to nursing staff who should prioritize, champion, and promote tablet provisioning.…”
Section: Discussionmentioning
confidence: 79%
“…1 2 21 Yet getting portals into the hands of hospitalized patients in a reliable manner remains a challenge for many hospitals. 8 11 12 Our findings suggested that the three strategies of establishing provisioning processes, having persistent unit-level champions, and actively promoting the distribution and use of MCB tablets can make a difference in unit provisioning performance.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…6,7 While these outcomes are promising, other researchers have focused attention on upstream factors that contribute to the success of inpatient portals, such as their use 6,[8][9][10] and usability, [11][12][13][14] the patient's experience of the portal, [15][16][17][18] and the care team's expectations of and experience with the portal. [19][20][21][22] This evidence provides insight into the nuanced ways in which different stakeholders interact with the technology. Importantly, the growing evidence regarding inpatient portals highlights the collaborative aspects of the technology between the patient and the care team with both optimistic potential and cautious pragmatism.…”
Section: Background and Significancementioning
confidence: 99%